Photocatalysis of xenobiotic organic compounds in greywater using zinc oxide nanoparticles: a critical review - Yashni, G.; Al‐Gheethi, Adel; Mohamed, Radin; Hossain, Md. Sohrab; Kamil, Amani Filzah; Abirama Shanmugan, Vikneswara (Water and environment journal : WEJ, 2021)
The direct discharge of raw bathroom greywater has increased the concentrations of various pollutants in the water bodies. Typically, greywater contains large quantities of xenobiotic organic compounds (XOCs) owing to an increase in consumption of personal care and bath products. Therefore, it urges for a suitable technology to eliminate these compounds from contaminated waters. Photocatalytic degradation using Zinc Oxide nanoparticles (ZnO NPs) has the potentiality to eliminate various XOCs. However, ZnO NPs have high tendency to aggregate, which may lower the photocatalytic degradation rate. Therefore, there is an urgency to modify ZnO NPs to overcome the limitation. The present review was conducted to determine a suitable method for the modification ZnO NPs. Besides, the potential of the modified ZnO NPs in degrading XOCs in greywater as a photocatalyst was also discussed.